2021
DOI: 10.1093/bbb/zbaa040
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C affects G0/G1 cell cycle and autophagy by downregulating of cyclin D1 in gastric carcinoma cells

Abstract: Vitamin C has re-emerged as a promising anticancer agent. This study attempts to analyze the differential gene expression of profiles GSE11919 to look for some clues, and the most significant cell cycle pathway caused by vitamin C was identified by integrated bioinformatics analysis. Inspired by this, we investigated the effect of vitamin C treatment on gastric carcinoma cells by detection of cell cycle, apoptosis, and autophagy. Vitamin C significantly elevated the percentage of cells at G0/G1 phase, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Recent clinical trials found that high-dose IV infusions of ascorbate (1.5-2.2 g/kg, 3× weekly, over 6 weeks) combined with chemotherapeutic agents improved progression-free survival (PFS) or overall survival (OS) in some types of cancer without serious side effects [16,72,76,77]. Under the catalysis of endogenous or exogenous metals such as Fe 3+ , high-dose ascorbate produces large amounts of H 2 O 2 and increases the cellular stress levels, resulting in DNA damage, cell cycle arrest, apoptosis, and autophagy while inhibiting epithelial-mesenchymal transition (EMT) and angiogenesis [5,12,18,71,78]. Therefore, it is currently believed that the antitumor mechanism of ascorbate mainly utilizes its pro-oxidative activity rather than antioxidative activity in most cancer cells [70].…”
Section: Ascorbate In Gynecological Cancersmentioning
confidence: 99%
“…Recent clinical trials found that high-dose IV infusions of ascorbate (1.5-2.2 g/kg, 3× weekly, over 6 weeks) combined with chemotherapeutic agents improved progression-free survival (PFS) or overall survival (OS) in some types of cancer without serious side effects [16,72,76,77]. Under the catalysis of endogenous or exogenous metals such as Fe 3+ , high-dose ascorbate produces large amounts of H 2 O 2 and increases the cellular stress levels, resulting in DNA damage, cell cycle arrest, apoptosis, and autophagy while inhibiting epithelial-mesenchymal transition (EMT) and angiogenesis [5,12,18,71,78]. Therefore, it is currently believed that the antitumor mechanism of ascorbate mainly utilizes its pro-oxidative activity rather than antioxidative activity in most cancer cells [70].…”
Section: Ascorbate In Gynecological Cancersmentioning
confidence: 99%
“…As one of the clinically common digestive tract malignant tumors, gastric cancer ranks 2 nd among all tumors in terms of mortality rate, seriously affecting the life health and quality of life of patients 1 . Gastric cancer is characterized by insidious onset and rapid progression, and patients often have already been at middle and advanced stages when diagnosed, so early detection, diagnosis and treatment are crucial for improving the treatment outcomes and survival quality 2 .…”
Section: Introductionmentioning
confidence: 99%